2015
DOI: 10.1136/jnnp-2015-310853
|View full text |Cite
|
Sign up to set email alerts
|

Management of spontaneous intracranial hypotension – Transorbital ultrasound as discriminator

Abstract: ObjectiveSpontaneous intracranial hypotension (SIH) is most commonly caused by cerebrospinal fluid (CSF) leakage. Therefore, we hypothesised that patients with orthostatic headache (OH) would show decreased optic nerve sheath diameter (ONSD) during changes from supine to upright position.MethodsTransorbital B-mode ultrasound was performed employing a high-frequency transducer for ONSD measurements in the supine and upright positions. Absolute values and changes of ONSD from supine to upright were assessed. Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
(25 reference statements)
5
49
1
3
Order By: Relevance
“…). A total of 34 studies provided mean values for ONSD measurement . The pool of mean ONSD measurements was 4.78 mm (95% CI, 4.63‐4.94 mm; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…). A total of 34 studies provided mean values for ONSD measurement . The pool of mean ONSD measurements was 4.78 mm (95% CI, 4.63‐4.94 mm; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously (3,5), transorbital US in the supine and upright positions was performed first (6). Native MRI of the entire spine, including sagittal T1-and T2-weighted imaging and an isotropic three-dimensional T2-weighted turbo spinecho sequence with fat saturation was followed by intrathecal gadolinium-enhanced MRI of the spine.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…The measure of the superior ophthalmic vein diameter by color Doppler flow has been proposed by Chen et al According to the author, a low blood flow in theses veins could reflect the low CSF pressure volume. Fichtner et al demonstrated a significant decrease of optic nerve sheath diameter measured by transorbital ultrasound in spontaneous intracranial hypotension (SIH) from supine to upright position . The author also confirmed a significant change of this diameter in SIH before and after microsurgical sealing of the cerebrospinal fluid leak .…”
Section: Discussionmentioning
confidence: 88%